Steel Structures Research Update: Structural Fire Engineering - Liu, Judy (Engineering Journal, 2021)
Across the United States, researchers are making exciting discoveries and advances in structural fire engineering. Eleven of the leading scholars in the field are featured. Brief research highlights are organized by the topic areas of behavior and design of steel and composite structures for fire, fire following earthquakes, and performance-based fire engineering. For each individual, related steel and fire research is also noted. Meanwhile, due to timing and circumstances, there are structural fire engineering researchers who do not appear in this article. You may find some of their structural steel research in past articles or perhaps a future research update.